2021
DOI: 10.1021/acs.est.0c08772
|View full text |Cite
|
Sign up to set email alerts
|

Donnan Dialysis-Osmotic Distillation (DD-OD) Hybrid Process for Selective Ammonium Recovery Driven by Waste Alkali

Abstract: This work proposed an innovative and energy-efficient Donnan Dialysis (DD) and Osmotic Distillation (OD) hybrid process for alkali-driven ammonium recovery from wastewater. The efficiency and feasibility of ammonium removal and recovery from synthetic and real wastewater using NaOH and waste alkali were investigated. Ammonium in the feed first transported across the cation exchange membrane and accumulated in the receiver chamber. It is then deprotonated as ammonia, passing through the gas permeable membrane a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 61 publications
(121 reference statements)
0
14
0
Order By: Relevance
“…As shown in Figure d, we found that the removal efficiency of NH 4 + -N reached 90% after acid absorption for 12 h and almost 100% when the run time was increased to 24 h. This means that the recovery efficiency of NH 4 + -N was close to 100% during the whole GMAR process, which had a stable pH value to ensure that the armor-structured NFM was not wetting. The energy consumption of this technique was estimated at 2.24 kWh kg –1 N by Method S10, lower than 10.3 kWh kg –1 N for the Haber–Bosch process . The total NH 4 + -N concentration in the illustration further confirmed that NH 4 + -N in the feed solution was almost completely recovered.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…As shown in Figure d, we found that the removal efficiency of NH 4 + -N reached 90% after acid absorption for 12 h and almost 100% when the run time was increased to 24 h. This means that the recovery efficiency of NH 4 + -N was close to 100% during the whole GMAR process, which had a stable pH value to ensure that the armor-structured NFM was not wetting. The energy consumption of this technique was estimated at 2.24 kWh kg –1 N by Method S10, lower than 10.3 kWh kg –1 N for the Haber–Bosch process . The total NH 4 + -N concentration in the illustration further confirmed that NH 4 + -N in the feed solution was almost completely recovered.…”
Section: Resultsmentioning
confidence: 69%
“…The energy consumption of this technique was estimated at 2.24 kWh kg −1 N by Method S10, lower than 10.3 kWh kg −1 N for the Haber−Bosch process. 27 The total NH 4 + -N concentration in the illustration further confirmed that NH 4 + -N in the feed solution was almost completely recovered. In addition, negligible CODcr was observed in the absorbent solution and no TP was detected (Figure 5e), which ensured the high purity of the recovered ammonium solution.…”
Section: Corrosion Resistance Mechanism Of Armor-structured Nfm In Th...mentioning
confidence: 59%
See 2 more Smart Citations
“…Breytus [9] showed the recovery of nitrate at 3 mM using Selemion, Neosepta and Fumatech membranes. Furthermore, Chen [10] studied the feasibility of ammonium recovery at 5-50 mM using using Selemion and Neosepta membranes and developed the process further by integrating Osmotic Distillation with a Donnan dialysis process [11]. Rodriguez [12] used Donnan dialysis to enhance the recovery of ammonia by electrodialysis and reduce energy consumption at 140 mM using Nafion membranes.…”
Section: Introductionmentioning
confidence: 99%